Distribution of elemental compositions of zeolite quarries and calculation of radiogenic heat generation - Turhan, S.; Tokat, S.; Kurnaz, A.; Altıkulaç, Aydan (Informa UK Limited, 2020)
The effectiveness ofthe use of zeolites in different industrial processes depends on their physical-chemical properties that are distinctly connected to their geological deposits. In this study, ma...
Keywords: Rdes; Zeolite; Major Oxides; Radiogenic Heat Generation; Thorium; Uranium; Eco-Toxic Metal; G&#246